Socotracris kleukersi n. gen. n. sp., a new troglobitic cricket from Socotra (Yemen) (Orthoptera: Grylloidea, Phalangopsidae) - Desutter-Grandcolas, Laure; Felix, Rob P. W. H. (Zootaxa, 2012)
The cricket Socotracris kleukersi n. gen., n. sp., collected in a cave at Wadi Zerik, Diksam Plateau, Socotra, Yemen is described. The genus and species are characterized by male and female genitalia and external morphology.